Functional Capacity Needs Assessment for The Agroforestry Researchers in Agricultural Innovation System (SAARC Journal of Agriculture, 2021)
Capacity needs assessment (CNA) is a procedure of assessing genuine existing capacity gaps within group members concerning knowledge, skills, strengths, weaknesses, opportunities, threats, assets, and supplementary elements obligatory for them to accomplish the pre-specified objectives. This study was undertaken to evaluate the existing capacity gaps among agroforestry researchers’ group through a closed and structured questionnaire with the six different topics consisting 24 different indicators to evaluate the existing capacity gaps among 30 participants involved with agroforestry research from different universities and the National Agricultural Research Institutes using MS Excel data schoring sheets during November 2018 to February 2019. The study focuses different functional capacity, like, capacity to navigate the complexity, collaboration, learning and reflection, engage in strategic and political processes. Age, sex, education, and occupation were the independent variables used for functional capacities. Among all the age groups, above 55 years old agroforestry researchers secured the highest score in most of the topics. Based on the analysis of the scores, the existence of opportunities to better know each other and improve collaboration recorded the highest score (2.59) which considered the major capacity strengths, and understanding of knowledge flows recorded the lowest score (1.65), which was major capacity weaknesses of the niche, individually. Within them, females participant reported greater responsible leadership and more cooperative among each other. This research concluded that agroforestry researchers need strong collaboration and well known to each other for minimize the capacity gaps in agroforestry research. The tudy suggested to estabilish “National agroforestry research and development Institute” for effective and efficient agroforestry research and development by the government of Bangladesh and the concern ministry.SAARC J. Agric., 19(1): 269-279 (2021)